Emerging insights into the structure and function of ionotropic glutamate delta receptors. (7th December 2020) - Burada, Ananth Prasad; Vinnakota, Rajesh; Bharti, Pratibha; Dutta, Priyanka; Dubey, Neelima; Kumar, Janesh
Abstract : Glutamate delta‐1 (GluD1) and delta‐2 (GluD2) receptors belong to the orphan GluD subfamily of ionotropic glutamate receptors (iGluRs). GluDs were classified as ionotropic glutamate receptors based on their sequence similarity. Two decades after these GluDs were first cloned they are still considered "orphan" due to a lack of knowledge of the endogenous ligands that can activate them. Nevertheless, they are crucial for synapse formation, maturation and maintenance of CNS functions, and are implicated in multiple neuronal disorders, including schizophrenia, autism spectrum disorder and depressive disorders. Over the last decade significant discoveries have been made, include role of GluD receptors in mediating trans‐synaptic interactions and their unique non‐swapped architecture, which is distinct from other ionotropic glutamate receptors. Also, the prospect of GluD ionotropic activity being regulated by direct interaction with metabotropic glutamate receptors is exciting. These discoveries will likely drive the field in the future, providing direction to GluD research. LINKED ARTICLES: This article is part of a themed issue on Structure Guided Pharmacology of Membrane Proteins (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.14/issuetoc